Fulfilling Child Rights Post-Divorce in Religious Courts Based on People's Economic Factors after Pandemic - Nurmala Nurmala; Qadariyah Barkah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This writing aims to understand and analyze the Implementation and Obstacles of the Letter of the Directorate General of the Religious Courts Number 1669/DJA/HK.00/5/2021 Concerning the Enforcement of Guarantees to Protect the Rights of Women and Children Post-Divorce, bearing in mind that the community's economy after the pandemic will impact post-divorce children's rights at the Tulang Bawang Tengah Religious Court. This writing uses normative qualitative research methods with rule and case study approaches. The results of the first study found that the Implementation of the Letter of the Director General of the Religious Courts Number 1669/Dja/Hk.00/5/2021 concerning Guarantees for the Fulfillment of Children's Rights Post-divorce at the Tulang Bawang Tengah Religious Court after the pandemic has fulfilled the spirit of fulfilling children's rights after divorce on a few notes. The results of the second study found inhibiting factors such as the Petitum for divorce cases not entirely containing demands for fulfilling children's rights after divorce because the Petitum for divorce cases did not include the fulfilment of the rights of women and children after divorce, Determining the value of living for wives and children due to divorce which still varies, Aspects of implementing the decision (execution) if one of the parties is not present, and the Judge's understanding of the Ultra Petitum Partium Principle.